Eksplorasi Kebutuhan Teknologi MPOS untuk Mendukung Pengembangan UMKM di Kabupaten Takalar - Sukarana, Murdiani; Anas, Muhammad; Machmury, Andri (Jurnal Media Informatika, 2024)
This study explores the benefits and challenges of using Mobile Point of Sale (MPOS) in the UMKM sector in Takalar Regency, focusing on 8 out of 23 businesses that have adopted this technology. The research methodology involved in-depth interviews with UMKM owners and managers to identify how MPOS affects their operations. The main findings indicate that MPOS significantly contributes to operational efficiency, particularly in transaction management and accounting. Benefits such as ease of transaction tracking and a variety of payment options enhance customer satisfaction and expedite the checkout process. However, challenges such as the need for basic skills, additional costs, and reliance on stable internet connections remain obstacles. In conclusion, although MPOS offers many advantages, successful adoption requires good technological infrastructure and adequate staff training. Recommendations include enhancing features and support to address existing challenges and encourage broader MPOS adoption in UMKM